Quality maintenance Tropical Plants - Dias, Gláucia Moraes (Ornamental Horticulture, 2016)
The climatic characteristics of the country favor the cultivation of tropical flowers. The continued expansion of this market is due the beauty, exoticit nature and postharvest longevity of flower. However, little is known about the postharvest of tropical plants. Therefore, this paper provides information on harvest, handling and storage of cut tropical plantspostharvest, storage temperature, conditioning solution.